A novel method for assessing patients with schizophrenia and their first‐degree relatives by increasing cognitive load of visuo‐spatial working memory. (7th September 2018) - Soni, Sunaina; Muthukrishnan, Suriya Prakash; Sood, Mamta; Kaur, Simran; Mehta, Nalin; Sharma, Ratna
Abstract: Introduction: In patients with schizophrenia, social and functional outcome is determined by the cognitive impairment. Assessment of visuo‐spatial working memory (VSWM) which can simulate the day‐to‐day activities by simultaneous involvement of various elements of working memory may reflect disorganized thinking and fragmentation of thoughts in schizophrenia. Methods: Thirty‐six patients with schizophrenia, 29 first‐degree relatives of patients, and 25 healthy controls performed a VSWM task with three memory loads (comprising three pairs, six pairs, and eight pairs of abstract pictures). They were administered Hindi version of the Mini Mental State Examination, Scale for the Assessment of Negative Symptoms and Scale for the Assessment of Positive Symptoms, and Edinburgh handedness inventory. Results: Patients (mean age 27.29(5.98) years) committed significantly higher number of errors than healthy controls (mean age 26.76(6.08) years) in load 3 ( P  = 0.012) and total errors ( P  = 0.018). Within all the groups, errors in load 3 were significantly higher than in load 2. Significant correlation was observed between years of education ( r  = −0.388, P  = 0.021), treatment duration ( r  = −0.880, P  < 0.001), negative symptoms scores ( r  = 0.345, P  = 0.039), and the total errors committed by patients. Discussion: Visuo‐spatial working memory was impaired in schizophrenia with increasing cognitive load with no difference in search time between the groups.